(untitled) - Heyne, Paul (Chicago, Illinois, 1983)
This text goes beyond explaining the basic principles of micro- and macroeconomic analysis by showing readers how to apply these principles as tools. The authors expose a method of reasoning that encourages readers to think like an economist through example and application. They also show readers how not to think, by exposing errors in popular economic reasoning.
Keywords: Economics